The Role of Epidermal Growth Factor Receptor Mutations and Epidermal Growth Factor Receptor-Tyrosine Kinase Inhibitors in the Treatment of Lung Cancer - Chang, Shih-Chieh (Molecular Diversity Preservation International (MDPI), 2011)
Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small-cell lung cancer (NSCLC) cases comprise approximately 85% of the lung cancer cases. Before the era of target therapy, platinum-based doublet chemotherapy only led to a median survival of 8–9 months and a one-year survival of 30%–40% in patients with advanced NSCLC. In July 2002, gefitinib, a small-molecule epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI), was approved for the treatment of patients with advanced NSCLC in Japan. After the widespread use of gefitinib in the treatment of NSCLC, there have been many new studies regarding the association between the clinical anticancer efficacy of gefitinib and the somatic EGFR mutation status in patients with NSCLC. This article summarizes the role of EGFR mutations in lung cancer and the use of EGFR antagonists in the treatment of lung cancer and its associated adverse effects.